The influence of COVID-19 pandemic on secondary prevention in non-COVID patients with cardioembolic stroke - Lučić-Prokin Aleksandra L.; Bogdanović Milan M.; Pustahija Tatjana L.; Stamenković Marija S. (Hospital Pharmacology)
Introduction: Since March 2020, when the World Health Organization declared the global pandemic of the Coronavirus disease 2019 (COVID-19), an era of great challenges for the entire healthcare system has begun. A new organization of the healthcare system was needed to balance care not only for cases tested positive for COVID-19, but also for those that did not. Data indicate a reduction in the functioning of stroke units, a decrease in neuroimaging diagnostic procedures, and changes in therapeutic interventions for stroke patients. Aim: This research investigates the assumption that these changes in medical care have affected the secondary prevention of cardioembolic stroke (CS) in non-COVID patients. Material and Methods: A cross-sectional study was conducted among 338 out of 1,928 non-COVID patients with CS and non-valvular atrial fibrillation (NVAF), comparing demographic, therapeutic recommendations between the period before and during the COVID-19 pandemic. Over a five-year period, data of the possible complications of therapeutic management for secondary stroke prevention were collected. Results: Among two groups, only chronic renal insufficiency emerged as a significant risk factor during COVID-19 (p=0.0365), while previous stroke was characteristic of the first period, before COVID-19 pandemic (p=0.0081). The most common therapeutic recommendations for secondary prevention of CS with NVAF included apixaban (p=0.0336) and bridging therapy: low-molecular weight heparin with acetylsalicylic acid (LMWH+ASA) (p=0.0011), both during the COVID-19 period. Complications were registered in 20 (8%) patients. Although not statistically significant, the highest proportion of systemic and neurological complications occurred in patients using dabigatran (25%) Recurrent stroke was registered in 20% of patients using apixaban, while 15% patients using rivaroxaban had systemic bleeding (15%). Conclusion: Our results demonstrate preserved stroke care quality during the COVID-19 time period. It is crucial to carefully evaluate the possible causes of any ischemic stroke, anticoagulant therapy with direct oral anticoagulants is the mainstay of NVAF management of CS stroke with the dominance of apixaban and bridging therapy. No intracranial bleeding was noted.